Lung Cancer Patients’ Profile in Dr Soetomo General Hospital Surabaya 2016 - 2017: Newest Report - Sita Ro'yul Aini; Laksmi Wulandari; Susilowati Andajani (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: Lung cancer is the leading cause of cancer death in the world, its 5 years survival rate is only 17%, whereas its incidence is the first most in men and third in women.Methods: This research was a descriptive observational study. The samples were 240 patients of lung cancer in Poly Oncology Dr. Soetomo General Hospital Surabaya 2016-2017. Sampling technique was non-random sampling (consecutive sampling). The variables were: age, sex, smoking habits, type of lung cancer, type of mutation, stage, symptoms, Vena Cava Superior syndrome, and therapy. The data analyzed were analyzed descriptively.Results: Patients mostly at age 51-55 and 56-60 years old (18% each). Ratio men and women are 1,7:1. In all type of lung cancer, men are dominant than women and mostly patients is active smoker. Ephidermal Growth Factor Receptor (EGFR) mutation found in adenosquamous (75%) and adenocarcinoma (65%). Most patients diagnosed at advance stage. Most symptoms are cough (70.4%), dyspnoea (50%), and chest pain (49.2%). Vena Cava Superior Syndrome (VCSS) found in adenocarcinoma (75%) and squamous cell carcinoma (25%). In adenocarcinoma and adenosquamous, patients commonly got targeted therapy.Conclusion: Lung cancer patients: 1) Men tend to be exposed to younger than women, 2) ratio men and women is 1.7:1 and most type in lung cancer is adenocarcinoma 3) mostly patients is active smoker, 4) EGFR mutation tent to be in women with adenocarcinoma, 5) most stage is stage IV, 6) most symptoms is cough, 7) Vena Cava Superior Syndrome is in adenocarcinoma (75%) and carcinoma cell squamous (25%), 8) patients’ therapy mostly with targeted therapy followed by chemotherapy.